Antiparasitic activity of methanol extracts and isolated fractions from caribbean sponges (2001)
ABSTRACT: Methanolic extracts from eight Caribbean sponges (Demospongy Class, Filo Porifera) were evaluated against several selected parasites. The sponges studied were Ircinia strobilina, Ircinia felix, Ircinia campana, Xestospongia proxima, Xestospongia muta, Agelas conifera, Agelas clathrodes and Niphates erecta. The parasites used as bioindicators were Trypanosoma brucei, Trypanosoma cruzi, Leishmania infantum, Leishmania panamensis Plasmodium falciparum Itg2 and Plasmodium falciparum Ghana. The most active extracts were those obtained from the Ircinia felix, Ircinia campana and Xestospongia proxima sponges. The chromatographic fractionations of the methanolic extracts of the Ircinia felix and Ircinia campana sponges, allowed to isolate several fractions, of which those that showed the highest activity against amastigotes of Leishmania panamensis, contain complex mixtures of 5 & 8 & -epidioxysteols, according to the NMR analysis. -1H and HPLC. On the other hand, the most active fraction against Plasmodium falciparum Itg2 was a fraction obtained from the I. felix extract, which did not show evidence of the presence of 5 & 8 & -epidioxysteols or seterterpenic tetronic acids.